Impact of participatory video-based extension and posters on awareness, knowledge, and adoption of climate-smart agricultural practices: Insights from women farmers in Gujarat, India - Barooah, Prapti; Alvi, Muzna; Ringler, Claudia (International Food Policy Research Institute, 2023)
Climate-smart agriculture (CSA) is critical for reducing smallholder farmers’ vulnerability and enhancing their capacity to cope with the adverse impacts of climate change. Constraints to information and extension access — especially among women farmers, who play a vital role in Indian agriculture — are increasingly acknowledged as a barrier for widespread adoption of CSA practices. This note summarizes results from a study implemented among smallholder women farmers in rural Gujarat, India, to assess the effectiveness of a participatory video and poster extension intervention on increasing awareness, knowledge, and adoption of CSA practices. The findings sug gest that videos and posters are a viable information delivery mechanism for promoting awareness around CSA practices but should be supplemented with additional capacity development, access to financial resources, and labor-sharing arrangements.